2011
DOI: 10.2174/1875043501104010028
|View full text |Cite
|
Sign up to set email alerts
|

Wharton's Jelly Mesenchymal Stem Cells as Off-The-Shelf Cellular Therapeutics: A Closer Look into their Regenerative and Immunomodulatory Properties

Abstract: Mesenchymal stem/stromal cells (MSCs) are isolated from most post-natal tissues and are broadly reported to have similar immuno-phenotype, mesenchymal lineage-differentiation potential and bio-distribution in peri-vascular niches. Thus, several stromal substitutes of bone marrow mesenchymal stem cells (BMMSCs) are being considered for regenerative therapy. Wharton's jelly mesenchymal stem cells (WJMSCs) seem to be the most promising alternative because of easy donor accessibility, high proliferative capacity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…Their potential results from their ease of isolation without risk to the donor, low immunogenicity, ability to differentiate towards chondrocytes, capacity for self-renewal and low risk of transfer of bacterial or viral infection [1315]. Flow cytometric analysis of isolated WJ-MSCs in this study showed high expression of human MSC markers and a lack of hematopoietic protein on the surface.…”
Section: Discussionmentioning
confidence: 85%
“…Their potential results from their ease of isolation without risk to the donor, low immunogenicity, ability to differentiate towards chondrocytes, capacity for self-renewal and low risk of transfer of bacterial or viral infection [1315]. Flow cytometric analysis of isolated WJ-MSCs in this study showed high expression of human MSC markers and a lack of hematopoietic protein on the surface.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, administration of immunosuppressive drugs is not required, thereby protecting the patient against their side effects. Besides mechanisms described above, immunoprivilege of WJ-MSC depends on immunosuppressive functions mediated by the wealth of paracrine factors as well as cell-cell contact (reviewed in detail in Jyothi Prasanna and Jahnavi [ 84 ] and Ma et al [ 85 ]).…”
Section: More Differences Between Adult and Wharton's Jelly Derivementioning
confidence: 99%
“…The isolation efficiency of WJMSCs 26 was greater than that of bone marrow 27 or adipose tissue 28 . WJMSCs also exhibit higher proliferative capacity 29 , abundant production of growth factors 30 , and lack of immunogenicity 31 32 .…”
Section: Discussionmentioning
confidence: 99%